System Coverage and Capacity Analysis on Millimeter-Wave Band for 5G Mobile Communication Systems with Massive Antenna Structure - Jun Suk Kim; Jae Sheung Shin; Sung-Min Oh; Ae-Soon Park; Min Young Chung (International Journal of Antennas and Propagation)
The use of a millimeter-wave band defined as a 30–300 GHz range is significant element for improving performance of 5th generation (5G) mobile communication systems. However, since the millimeter-wave signal has peculiar propagation characteristics especially toward non-line-of-sight regions, the system architecture and antenna structure for 5G mobile communications should be designed to overcome these propagation limitations. For realization of the 5G mobile communications, electronics and telecommunications research institute (ETRI) is developing central network applying various massive antenna structures with beamforming. In this paper, we have introduced the central network and evaluated the system coverage and capacity through C++ language-based simulations with real geospatial information.